2016
DOI: 10.1016/j.jid.2015.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal LTA-Induced miR-143 Inhibits Propionibacterium acnes-Mediated Inflammatory Response in Skin

Abstract: Staphylococcus epidermidis (S. epidermidis) plays a critical role in modulating cutaneous inflammatory responses in skin. Although S. epidermidis has been shown to co-colonize with Propionibacterium acnes (P. acnes) in acne lesions, it is unclear whether S. epidermidis is involved in the regulation of P. acnes-induced inflammatory responses. In this study, we demonstrated that S. epidermidis inhibited P. acnes-induced inflammation in skin. P. acnes induced the expression of interleukin-6 and tumor necrosis fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 33 publications
1
67
0
Order By: Relevance
“…aureus infection exclusively increased the levels of mRNAs encoding SLIT2 (slit homolog 2 protein), the micro-RNA miR-143 and C1QTNF3 (C1q and tumor necrosis factor related protein 3), all known to counteracting LPS induced inflammation. SLIT2 inhibits NF-κB activation 38 , miR-143 downregulates TLR2 expression 39 while C1QTNF3 is a direct antagonist of TLR4 signaling by prohibiting binding of its ligand LPS 40 . RSPO3 (R-spondin-3) 41 and CTHRC1 (collagen triple helix repeat containing 1) 42 complete the list of inhibitory factors having exclusively been induced during the S .…”
Section: Resultsmentioning
confidence: 99%
“…aureus infection exclusively increased the levels of mRNAs encoding SLIT2 (slit homolog 2 protein), the micro-RNA miR-143 and C1QTNF3 (C1q and tumor necrosis factor related protein 3), all known to counteracting LPS induced inflammation. SLIT2 inhibits NF-κB activation 38 , miR-143 downregulates TLR2 expression 39 while C1QTNF3 is a direct antagonist of TLR4 signaling by prohibiting binding of its ligand LPS 40 . RSPO3 (R-spondin-3) 41 and CTHRC1 (collagen triple helix repeat containing 1) 42 complete the list of inhibitory factors having exclusively been induced during the S .…”
Section: Resultsmentioning
confidence: 99%
“…In human neonates, there is an increase in TLR2 expression over the course of S. epidermidis sepsis (Viemann et al, 2005), however, a TLR-stimulated immune system was reported to be less proficient in eliciting multiple cytokine responses in neonates compared to adults (Kollmann et al, 2009). S. epidermidis PIA (Stevens et al, 2009), PSMs (Hajjar et al, 2001), and lipoteichoic acid (LTA) (Xia et al, 2016) have been claimed to be effectors of TLR2. However, studies with PIA and PSMs were not verified with isogenic mutants; and as for LTA, there has been recent evidence indicating that staphylococcal lipopeptides rather than LTA are the real immune-stimulatory agents (Hashimoto et al, 2006).…”
Section: Immunity Against S Epidermidis During Sepsismentioning
confidence: 99%
“…More and more researches have focused on the potential functions of circRNAs that as miRNA sponges in parental gene expression regulation to influence physiologic processes as well as disease . More recently, a small number of miRNAs such as miR‐143 and miR‐338‐3p have been firstly demonstrated as a major player in the regulation of inflammatory responses in acne . To our knowledge, this study reported for the first time the comprehensive expression profiles of circRNAs and their potential function in patients with severe acne.…”
Section: Discussionmentioning
confidence: 86%
“…2,6,7 More recently, a small number of miRNAs such as miR-143 and miR-338-3p have been firstly demonstrated as a major player in the regulation of inflammatory responses in acne. 8,9 To our knowledge, this study reported for the first time the comprehensive expression profiles of circRNAs and their potential function in patients with severe acne. Using highthroughput RNA sequencing and bioinformatics analysis, 538 differentially expressed circRNAs were detected, in which 271 circRNAs are significantly upregulated and 267 circRNAs are downregulated in lesional skins compared with their paired adjacent non-lesional skins (n = 3).…”
Section: Discussionmentioning
confidence: 88%